Makna Sosial Haji Pada Masyarakat Desa Pattiro Kecamatan Bangkala Barat Kabupaten Jeneponto - Ita Puspita; Yumriani Yumriani; Nursalam Nursalam (Universitas Lambung Mangkurat, 2024)
This research aims to analyze the social meaning of Hajj and the community in Pattiro. Research focusing on Pattiro Village was carried out using a qualitative approach. The data collection process through in-depth interviews and analyzed by four stages of data collection, data reduction, data assessment and drawing conclusions. The research results show that the social meaning of the Hajj in the Pattiro comes from the community's perception of the heavy Hajj procession, so that everyone who goes through it has a high spiritual experience. The social status of Hajj indicated by the reward in various social activities. Another form of appreciation is giving the title of nobility (Karaeng or Daeng) by the leadership qualities or are a role model for society.